Characterization of weakly Berwald fourth root metrics - Abazari, N.; Khoshdani, T. R. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 514.7 In recent studies, it is shown that the theory of fourth root metrics plays a very important role in physics, theory of space-time structures, gravitation, and general relativity. The class of weakly Berwald metrics contains the class of Berwald metrics as a special case. We establish the necessary and sufficient condition under which the fourth root Finsler space with an (α, β)-metric is a weakly Berwald space.